Investigating vertical transmission and maternofoetal outcomes in pregnant women with COVID-19: a case-control study from Pakistan - Samra Khan,; Sharmeen Fayyaz,; Muhammad Irfan,; Muhammad Shakeel,; Zaib Un Nisa Talbani,; Sajida Imran,; Muhammad Khalid Shafi,; Imtiaz Bashir,; Ishtiaq Ahmed Khan, (Journal of the Pakistan Medical Association, 2024)
Objective: To estimate the frequency of severe acute respiratory syndrome coronavirus-2 among pregnant women, the impact in terms of obstetrical and clinical outcomes and vertical transmission to the neonates. Method: The prospective, case-control study was conducted at Zainab Panjwani Memorial Hospital, Karachi, from March to December 2021, and comprised pregnant women regardless of gestational age who exhibited symptoms or had a suspicion of exposure to any confirmed coronavirus disease-2019 individual. They were screened for severe acute respiratory syndrome coronavirus-2 infection using polymerase chain reaction or serology. Those who tested negative were designated as control group A, while who had a positive serology result along with a negative polymerase chain reaction were taken as recovered case group B1, and those who tested positive for polymerase chain reaction were called the positive case group B2. Groups B1 and B2 were followed up till delivery. The clinical presentation of coronavirus disease-2019 infection in pregnancy and its obstetrical and neonatal outcomes was assessed. Products of conception were tested for the detection of the severe acute respiratory syndrome coronavirus-2 genome. The viral genome from group B2 cases was sequenced to confirm vertical transmission. Data was analysed using GraphPad Prism V8. Results: Of the 139 pregnant women, 74(53.2%) were in group A with mean age 25.87±6.90 years, 49(35.3%) were in group B1 with mean age 25.53±7.02 years, and 16(11.5%) were in group B2 with mean age 27.12±5.03 years. The gestational age at which termination of pregnancy occurred was 38.3±1.26 weeks in group B1 and 38.3±1.85 weeks for group B2. There were 96 neonates across the 3 groups. Of the 11(11.45%) neonates in group B2, 1(9.09%) had postnatal transmission of severe acute respiratory syndrome coronavirus-2 and this mother-neonate case was taken as the Indexed case. The severe acute respiratory syndrome coronavirus-2 genome isolated from the neonate showed similar mutations as the viral strain infecting the mother. Conclusion: The risk of vertical transmission was found to be low. The severe acute respiratory syndrome coronavirus-2 genome was the same for both the mother and the neonate. Key Words: SARS-CoV-2, vertical transmission, pregnancy, COVID-19, Pakistan